IMPLEMENTASI AKAD IJARAH DALAM MEMBANGUN KEPERCAYAAN KONSUMEN PADA USAHA SEWA TENDA PONOROGO - Marlina, Isna; Rohman Albanjari, Fatkhur; Khusnul Rois, Adib (Berajah Journal, 2025)
This research aims to increase knowledge about the implementation of the Ijarah contract in the practice of renting outdoor equipment at Sewa Tenda Ponorogo to build consumer trust. This study is classified as a type of qualitative research of the Virtual Ethnography type conducted in Kadipaten Village, Babadan District, Ponorogo Regency. Research data were collected using interview techniques, observation and long-distance documentation. The results of the study concluded that the rental system carried out at the Sewa Tenda Ponorogo outdoor rental still uses conventional methods. Business owners, employees and consumers of Sewa Tenda Ponorogo also do not know what the Ijarah Agreement is, but in the implementation of the lease in accordance with the principles and provisions of ijarah including starting from Aqil or the person who rents the lease, sighat akad or ijab qabul, ujroh or rental fees and the benefits of ijarah itself. The existence of the Sewa Tenda Ponorogo rental business is very financially beneficial for business owners, then provides convenience for consumers to meet their outdoor equipment rental needs easily and at prices that are in accordance with the Ponorogo market. Consumers feel safe and comfortable when using Ponorogo Tent Rental services so they often rent again and become regular customers.